LEUKOCYTE PROFILE AND NEUTROPHIL-LYMPHOCYTE RATIO IN GOATS IN KAMPUNG JAWA, NORTH DENPASAR, BALI - Baihaqi, Daffa; Siswanto; Sukernayasa, I Wayan (Buletin Veteriner Udayana, 2025)
This study aimed to determine the leukocyte profile and neutrophil-ymphocyte ratio in goats that were temporarily kept before slaughter in Kampung Jawa, North Denpasar, Bali. A total of eight female goats were used as samples, with blood collected during the slaughter process and analyzed using conventional hematological methods. The results showed that the average total leukocyte count was 8.04×10³/µL, which was still within the normal range. The average leukocyte differential consisted of 45.75% neutrophils, 46.63% lymphocytes, 8.75% monocytes, 1.5% eosinophils, and 0% basophils. Based on these findings, neutrophils were within the normal range, lymphocytes showed a decrease, monocytes showed an increase, while eosinophils and basophils were within the normal values. The neutrophil-lymphocyte ratio was 2.79, which was higher than the reference value. Farmers are advised to improve management and environmental conditions, while future research should involve larger samples and cortisol analysis as a stress marker.